2004
DOI: 10.1177/0734242x04045428
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method for the Treatment of Waste Produced at a Dye and a Metal-Plating Industry Using Natural and/or Waste Materials

Abstract: The aim of this study was to develop cost-effective, appropriate solidification technologies for treating hazardous industrial wastes that are currently disposed of in ways that may threaten the quality of local groundwater. One major objective was to use materials other than cement, and preferably materials that are themselves wastes, as the solidification additives, namely using wastes to treat wastes or locally available natural material. This research examines the cement-based and lime-based stabilization/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Stabilization/Solidification (S/S) is known as one of the most popular techniques for the treatment of hazardous waste and it has been used for decades an encapsulation material, prior to the disposal of radioactive and hazardous wastes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization/Solidification (S/S) is known as one of the most popular techniques for the treatment of hazardous waste and it has been used for decades an encapsulation material, prior to the disposal of radioactive and hazardous wastes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the following period the values have stabilized and were around 7.5, due to mutual neutralization of the present materials, indicating that the leachates are not aggressive and corrosive in nature. Observing different mixtures it was concluded that pH values were not greatly affected by increased portion of the sludge [7,42]. In a similar manner conductivity was lower at the beginning of the test as the leachates were renewed every day.…”
Section: Figure 3 -Ph and Conductivity Measurements Of Collected Leacmentioning
confidence: 85%
“…Stabilization and solidification (S/S) is characterized as the best available technique for the treatment of hazardous and other waste types [7,8], and has been extensively used as the final treatment step prior to the disposal of industrial wastes. Typically, the stabilization processes also involve some form of the physical solidification [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various technologies have been developed to transform hazardous wastes to nontoxic forms or to reduce the potential release of toxic species into the environment (Conner 1990;Pereira, Pinero, and Vale 2001;Dermatas and Meng 2003;Samaras et al 2008;Lasheen and Ammar 2009). Recently, more attention is paid to the sludge stabilization process aiming to minimize the mobility of metals using various additives where the toxic constituents present in hazardous solid sludge are physically as well as chemically fixed to ensure the compliance with existing regulatory standards (Conner 1990;Dermatas et al 2004;Fatta et al 2004;Malviya and Chaudhary 2006;Montinaro et al 2007;Giergiczny and Kro´l 2008;Buj et al 2010). One of the promising binders is diatomaceous earth, occurring as artificial zeolites and natural sorbents (clinoptylolite), the addition of which can improve the physicochemical properties of the sewage sludge.…”
Section: Introductionmentioning
confidence: 98%